How Insurtech Can Close the Protection Gap in Emerging Markets - Holliday, Susan (International Finance Corporation, Washington, DC, 2019)
Insurance technology, better known as Insurtech, is a rapidly growing industry that is beginning to disrupt traditional insurance provision in advanced and emerging economies alike, and is creating opportunities and challenges for incumbents, start-ups, and investors. The opportunity offered by insurtech is particularly significant in emerging markets, where a large protection gap exists due to low insurance penetration. This has major development implications due to the fact that economic growth and insurance penetration are closely intertwined. Technology and new business models are necessary to close the protection gap in these markets, and companies will need to be able to innovate - either internally, by partnerships, or by investing - to seize the opportunity.